USING OUTDOOR LEARNING TECHNIQUE IN INCREASING STUDENTS’ ENGLISH EXPRESSION SKILL - Jusnidar Jusnidar; Wahyuddin Naro; St. Nurjannah Yunus Tekeng (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2021)
The objective of this research was to find out the effectiveness of outdoor learning technique in increasing students’ English expression skill at the second-grade students of a vocational school in Makassar. This research employed quasi-experimental namely non-equivalent control group design with pre-test and post-test. There were two variables in this research; they were independent variable (Outdoor Learning Method) and dependent variable (students’ English Expression skill). The population of this research was the second of a vocational school in Makassar which composes of 179 students. The sample of the research consisted of 40 students which was taken by using purposive sampling technique, 20 students from XI MMD as the experimental class and 20 students from XI RPL as control class. The instrument used in this research was test. The test was used in the pre-test and post-test. The mean score on the post-test (73.9) in the experimental class was higher than the mean score on the post-test (68.9) in the control class. The standard deviation on the post-test (7.7) in the experimental class and the standard deviation of the post-test in the control class (7.6). From the t-test, the researcher found that the value of the t-test (5.747) was higher than the t-table (2.042) at the level of significant 0.05 with degree of freedom (df) = 38. The effectiveness of Outdoor Learning method also can be seen from the effectiveness test, where the result of the test is 0.24(R<1). The data indicated that there was a significance difference between the students’ post-test in the experimental class and post-test in the controlled class. The result of hypothesis test showed that Outdoor Learning Method was significantly effective. Therefore, Outdoor learning method is effective in increasing students’ English expression skill.